Number of Factors in Growth Curve Modeling. Issue 6 (2nd November 2018) - Bentler, Peter M.
Abstract : Basic growth curve models parameterize the mean and covariance structure of a set of repeated measures by latent factors that represent the polynomial influences of time. In practice it may be hard to choose the number of factors, i.e., the order of the polynomial. Simple calculations are proposed to estimate this order.